Performance of wood ash blended reinforced concrete beams under acid (HCl), base (NaOH) and salt (NaCl) curing conditions - Tejo Manikanta, B; Ranga Rao, V; Achyutha Kumar Reddy, M (International Journal of Engineering and Technology, 2018)
Nowadays disposal of wood ash generated from various sources became a very challenging problem. Utilization of wood ash in cement and concrete was started from last 10 years. In this research, an attempt was done to examine the durability properties of reinforced cement concrete with 5, 10, 15 and 20 percentage replacement of cement with wood ash in concrete. The specimens with all proportions were cast, cured 28 days for one set specimens while another 3 set were cured in acid (HCl), base (NaOH) & salt (NaCl) conditions for 90 days. All specimens were tested to failure under loading frame of 500 kN capacity with 1 kN/sec as the rate of loading, weight loss, ultimate load, and deflection were determined. The better performance is shown by blended specimens against NaCl, NaOH and week resistance against HCl. The concrete with 5 percent replaced with wood ash can be used coastal regions as a result of greater resistance to against NaCl.
Keywords: Wood Ash; Durability; Flexure Strength; Weight Reduction and Deflection.